MODERN GLP-1 BASED PHARMACOTHERAPY FOR SEVERE ADOLESCENT OBESITY: CLINICAL PROMISE, SAFETY CONCERNS, AND ETHICAL CHALLENGES - Porwolik, Agata; Porwolik, Hanna; Cyran, Patryk; Szydłowski, Radosław; Bodera, Magdalena; Skotarski, Marek (International Journal of Innovative Technologies in Social Science, 2026)
Childhood obesity is an emerging worldwide health crisis, which has far-reaching harmful impacts on the health and development of affected adolescents (Hesketh et al., 2024; Li et al., 2024; Marcus et al., 2022). Innovative therapies such as glucagon-like peptide-1 receptor agonists (GLP-1RAs) have shown great promise as pharmacological intervention, with substantive clinical benefit to the population. This review provides a detailed synthesis of GLP-1RAs from the perspectives of their pharmacological mechanisms, clinical potential in adolescents, safety profiles and associated ethical and social considerations. The pharmacological rationale for GLP-1RAs is due to their ability to mimic the effect of endogenous GLP-1, a hormone which plays an important role in maintaining glucose homeostasis and in regulating appetite (Moiz et al., 2025; Muzurović et al., 2022). These agents promote glucose-dependent insulin secretion, reduce glucagon release and also slow gastric emptying, thereby attenuating glycaemic excursions after a meal and promoting satiety (Alharbi, 2025; Drucker, 2021; Shah & Vella, 2014). Importantly, GLP-1RAs also activate receptors in the central nervous system to reduce hunger and food intake, which result in weight loss of significant and sustained magnitude (Dailey & Moran, 2013; Hayes, 2012; Moiz et al., 2025). This multifaceted mechanism is the basis of their efficacy to treat both type 2 diabetes and obesity. Within the adolescent age group, GLP-1RAs have shown significant clinical potential especially with liraglutide and semaglutide.Liraglutide, approved for people aged 12-17 years, has led to better body mass index (BMI) z-score and clinically significant reduction in weight compared with placebo (Berman et al., 2023; Jensterle & Janež, 2021). Semaglutide, which is approved for adolescents 12+ years, continues to push the efficacy bar and confirmatory trials have reported mean BMI reductions of over 16% with a high prevalence of participants achieving significant weight loss (Weghuber, Barrett, et al., 2023; Weghuber, Kelly, et al., 2023). Beyond reducing weight, GLP-1RAs improve key metabolic markers - triglycerides, total cholesterol, HbA1c and systolic blood pressure - which reduces the risk of cardiovascular and type 2 diabetes in the long term (Silvia et al., 2021; Weghuber, Barrett, et al., 2023; Weghuber, Kelly, et al., 2023). Moreover, these medications improve weight-related quality of life, especially the physical comfort, which addresses the psychological burden of obesity in youth (Weghuber, Barrett, et al., 2023; Weghuber, Kelly, et al., 2023). Despite their efficacy, GLP-1RAs are a unique category of pharmacologic agents with regard to safety profile that requires close scrutiny. Frequently encountered adverse events are gastrointestinal in nature - nausea, vomiting, diarrhoea and constipation - generally being mild, transient and amenable to dose titration (Santos & Castro, 2025; Silvia et al., 2021). More serious issues include proven risks of cholelithiasis and acute pancreatitis, as seen in some trials (Weghuber et al., 2022; Woronow et al., 2022). A black box warning (defined by FDA) is used to alert clinicians to the potential risk of thyroid C-cells tumours, such as medullary thyroid carcinoma, based on rodent studies, and therefore require contraindication in certain clinical situations (Bezin et al., 2022; Kelly & Sipos, 2024; Pasternak et al., 2024).Long-term data on the effect of GLP-1RA on adolescent growth, pubertal development and neuropsychiatric outcomes (including suicidal ideation) are still sparse and the need for continued, rigorous surveillance (Bartkoski et al., 2025; Cooper et al., 2023). Ethical and societal considerations are very important when incorporating GLP-1RAs into the care of adolescents. Challenges include the need for truly informed consent, and respect for adolescent autonomy, in particular because of the chronic nature of therapy (Turhal & Bağlam, 2025; Viner et al., 2020). Dramatic increases in cost and poor insurance coverage create important equity issues, which may serve to exacerbate health disparities (Berman et al., 2023; Wright et al., 2023). Societal stigma against obesity and the potential for reinforcing a "weight-normative" paradigm or misuse for cosmetic purposes also need to be watched out for (Button et al., 2025; Cominato et al., 2021; Floegel‐Shetty, 2023). A holistic approach that goes beyond simply reducing weight to include but is not limited to metabolic health, psychological wellbeing, and quality of life is crucial to ethical and effective practice. In conclusion, GLP-1RAs have been shown to be a transformational approach in the management of severe obesity in adolescents, but their introduction into the clinic will need to be accompanied by a commitment to long-term safety studies and equitable and patient-centred care.